Disparity and convergence: Chinese provincial government health expenditures. - Jay Pan; Peng Wang; Xuezheng Qin; Shufang Zhang (PLoS ONE, 2013)
The huge regional disparity in government health expenditures (GHE) is a major policy concern in China. This paper addresses whether provincial GHE converges in China from 1997 to 2009 using the economic convergence framework based on neoclassical economic growth theory. Our empirical investigation provides compelling evidence of long-term convergence in provincial GHE within China, but not in short-term. Policy implications of these empirical results are discussed.